2022
DOI: 10.3390/ijerph192214981
|View full text |Cite
|
Sign up to set email alerts
|

Green Financial Reform and Corporate ESG Performance in China: Empirical Evidence from the Green Financial Reform and Innovation Pilot Zone

Abstract: Does the establishment of pilot zones for green finance reform and innovations in 2017 have an impact on the Environment, Social and Governance (ESG) scores of enterprises? This paper selects data from Chinese A-share listed companies from 2014–2020 and uses the differences-in-differences (DID) model to analyze the impact of green financial reform on the ESG scores of enterprises. The study shows that the establishment of the Green Financial Reform and Innovation Pilot Zone (GFPZ) policy helps enterprises to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Some scholars used the establishment of GFRIs as a natural experiment to explore the implementation effects of green finance policies. The establishment of GFRIs reduces enterprises' inefficient and excessive investment in the pilot zone, improves their investment efficiency (Yan et al, 2022), and helps enterprises obtain higher SEG scores through environmental, social, and governance mechanisms (Chen et al, 2022). The establishment of GFRIs improves enterprises' quality and quantity of green innovation (Zhang and Li, 2022).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Some scholars used the establishment of GFRIs as a natural experiment to explore the implementation effects of green finance policies. The establishment of GFRIs reduces enterprises' inefficient and excessive investment in the pilot zone, improves their investment efficiency (Yan et al, 2022), and helps enterprises obtain higher SEG scores through environmental, social, and governance mechanisms (Chen et al, 2022). The establishment of GFRIs improves enterprises' quality and quantity of green innovation (Zhang and Li, 2022).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The Green Financial Reform and Innovation Pilot Zones (GFPZ) policy's effect on the ESG ratings of Chinese A-share listed firms between 2014 and 2020 is examined in another study. The findings showed that the GFPZ policy raises ESG scores, which are mainly based on social responsibility, and helps businesses in the pilot zones do better financially and environmentally [17]. In 2023, Shao and Huang [111] reviewed China's green finance policy mix, showing a shift toward market-based approaches and greater private sector engagement, influenced by dynamic vertical interactions between different levels of government.…”
Section: Discussionmentioning
confidence: 99%
“…Although past research has examined the positive impacts of environmental social responsibility [ 53 , 54 , 55 ], limited research investigates how the mediating perspective of green commitment and the moderating perspective of institutional pressure affect the domain of employee sustainable behavior. Consequently, past research ignores the key position of green commitment and institutional pressures for pro-environmental behaviors.…”
Section: Discussionmentioning
confidence: 99%